If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -8x(-6) = 0 Reorder the terms for easier multiplication: 12 + -8 * -6x = 0 Multiply -8 * -6 12 + 48x = 0 Solving 12 + 48x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 48x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 48x = 0 + -12 48x = 0 + -12 Combine like terms: 0 + -12 = -12 48x = -12 Divide each side by '48'. x = -0.25 Simplifying x = -0.25
| 12e=216 | | 3/4=12/ | | 8a+6a-2=5 | | (7)(-2)= | | 6x-1+9x+8= | | (3x)(49)=(14x) | | -3(2t+3)=-33 | | 85f=685 | | 5v+x=w^2 | | 15p-5p+4=9 | | -10(s+1)=51 | | 0.72*c=7.5 | | 5x-3+2x=7x+7 | | 48/-16= | | 5x-1=231 | | 3+2(5x+6)=5 | | 5(4s+6)=130 | | h-10=27 | | 8x-19=4-7x | | -1470=-5x-210 | | 8(2l+7)=72 | | -(3+6)+2x=-(6+2)-3.3 | | 14z=18+12z | | -30-29= | | 5x+7=6z | | 12[x]1/3 | | 2y-3=5-s | | 14z=18+12m | | x^2+ab-ax-bx=0 | | 0=-5x-210 | | 2x+1=52 | | (u-8)*10=20 |